PENGEMBANGAN E-MODUL AKU ANAK MANDIRI AKU ANAK AMAN BERBASIS HUMAN SECURITY PADA SISWA KELAS 1 DI SEKOLAH DASAR - Ramadhanti, Nira; Husna Farhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an e-module titled "I Am an Independent Child, I Am a Safe Child" based on human security for first-grade elementary school students. The research was motivated by the continued occurrence of violence against children in learning environments and the lack of self-protection learning media for grade 1 under the Merdeka Curriculum. The method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at three schools: SDN Bahagia 05, SDN Bahagia 06, and SDN Kota Baru IX, involving 3 teachers and 90 first-grade students. The instruments included expert validation sheets and a Google Form for teacher responses. The results showed that the e-module development passed all stages of the ADDIE model. Expert validation results indicated an average feasibility rate of 94.6%, categorized as highly feasible. During implementation, students were very enthusiastic and able to understand self-safety concepts well. Additionally, teachers gave very positive responses to the use of the e-module. Thus, it can be concluded that the development of the e-module was successfully completed and declared feasible for use as a self-safety learning medium.